Enhancing Cloud Security: Implementing Zero Trust Architectures in Multi-Cloud Environments (International Journal of Scientific Research and Management (IJSRM), 2016)
As organisations are deploying multiple clouds to scale, gain flexibility and cost optimisation the challenge of securing these architectures grows exponentially. Conventional logical security platforms that are based on perimeters cannot effectively guard current complex cloud environments. Currently, however, there is a need to develop methods for their implementation, which refers to the Zero Trust Architecture (ZTA) approach with the overall slogan “Never Trust, Always Verify”. This security model means that any user, device, and network request is authenticated, authorized and monitored all the time irrespective of the source. In multi-cloud where applications, data and computing resources are located across various cloud service providers, use of Zero Trust lowers the risks of threats and cyber-attacks by minimizing the exposures that bad actors can exploit, and hardening control of entry to assets. Drawing on theory and research, this paper considers the advantages and disadvantages of the Zero Trust model, the processes that need to be completed to introduce it to the multi-cloud infrastructure, and possible case studies. Hence, Identity and Access Management, Micro-segmentation, and continuous monitoring can help the organization enhance the cloud security posture, and minimize compliance and risks related to sophisticated cloud environments.